The income elasticity gap and its implications for economic growth and tourism development: the Balearic vs the Canary Islands - Inchausti-Sintes, Federico; Voltes-Dorta, Augusto; Suau-Sanchez, Pere (Taylor & Francis, 2020)
The Balearic and the Canary Islands are two well-known tourism-led economies. They both experienced a tourism boom during the same decades, and, hence, they developed a similar productive-mix. Nevertheless, there are strong economic differences between the two regions. While the Balearic Islands enjoy a high GDP per capita, the Canary Islands show a more modest performance. The results of a panel data regression confirm our hypothesis that they differ substantially in terms of income elasticity of tourism. It is two times higher in the Balearic Islands than in the Canaries, which indicates the first is perceived as a more luxurious destination. Furthermore, the results of a dynamic computable general equilibrium model show that the Canaries would converge in GDP per capita with the Balearic Islands if they attracted tourists with a similar profile as the latter
Keywords: dynamic computable general equilibrium; tourism-led economies; economic growth; Income elasticity